Dry eye treatment optimization in patients prior to refractive surgery - S. N. Sakhnov; S. V. Yanchenko; A. V. Malyshev; Z. M. Blyagoz; G. A. Klimenova (Российский офтальмологический журнал)
Purpose. To evaluate the effectiveness of dry eye syndrome (DES) treatment in patients with meibomian gland dysfunction (MGD) before refractive surgery.Materials and methods. We examined 48 women (aged 29.6 ± 3.9 years) with myopia, DES, and MGD of noninfectious etiology before performing LASIK. Group 1 of these patients received presurgical correction of DES for 2 months, including instillation of 3 % trehalose as a bioprotector (Thealoz®; 3–4 times a day); application of 5 % dexpanthenol in the conjunctival cavity (before going to bed); eyelid hygiene (2 times per day), which included cleaning (Theagel®), warm compresses on eyelid area, massage of eyelid margin (Blephaclean wipes). Group 2 only received bioprotective and reparative therapy for 2 months. Testing included a standard ophthalmological examination; assessment of DES symptoms (OSDI scale, points); BUT test (sec) and Schirmer-1 test (Sh-1, mm); measuring the height of the lower tear meniscus (optical coherence tomography, μm); lissamine green staining with calculation of xerosis index by Bijsterveld (points); assessment of MGD severity (points). Processing of the results included calculation of M ± s; Wilcoxon t-test, Mann Whitney U-test.Results. A positive change of OSDI (decrease from 31.9 ± 2.9 to 8.71 ± 1.1 points), xerosis index (decrease from 4.71 ± 0.5 to 2.1 ± 0.3 points) and BUT test (increase from 4.14 ± 0.53 to 8.66 ± 0.93 sec) was significantly stronger in patients of group 1 (p < 0.05) in comparison with patients of group 2 (decrease in OSDI from 33.2 ± 3.1 to 15.6 ± 2.4 points; decrease of xerosis index from 4.75 ± 0.50 to 3.7 ± 0.5 points; BUT increase from 4.21 ± 0.47 to 6.05 ± 0.73 sec). Apparently, this was caused by a significant decrease in the severity of MGD (from 2.1 ± 0.3 to 0.9 ± 0.2 points) and a decrease in the severity of lipid deficiency due to eyelid hygiene in patients of group 1. In group 2, MGD severity change proved unreliable. Change of Sh-1 and the height of the lower tear meniscus was unreliable in all cases. Conclusion. The inclusion of eyelid hygiene (Theagel and Blephaclean) in the pre-surgery preparation of patients with DES and MGD leads to a more significant correction of eye surface condition compared to isolated bioprotective and reparative therapy, thus providing an opportunity of more favorable conditions for carrying out surgical correction of ametropia.